Simulation using discriminant analysis the course of pyoderma in men and women of western region of Ukraine depending on the characteristics of constitutional parameters of body = Моделювання за допомогою дискримінантного аналізу перебігу піодермій у чоловіків і жінок західного регіону України в залежності від особливостей конституціональних параметрів тіла - Yu. Ya. Kryvko; I. V. Gunas; R. S. Vastyanov; I. O. Chaplyk-Chyzho (Journal of Education, Health and Sport, 2016)
Kryvko Yu. Ya., Gunas I. V., Vastyanov R. S., Chaplyk-Chyzho I. O. Simulation using discriminant analysis the course of pyoderma in men and women of western region of Ukraine depending on the characteristics of constitutional parameters of body = Моделювання за допомогою дискримінантного аналізу перебігу піодермій у чоловіків і жінок західного регіону України в залежності від особливостей конституціональних параметрів тіла. Journal of Education, Health and Sport. 2016;6(6):599-605. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.56742